ZnS: Mn triboluminescence material, ZnS-based triboluminescence composite solid lubricating material, and preparation method and application of ZnS: Mn triboluminescence material and ZnS-based triboluminescence composite solid lubricating material
The surface of ZnS particles is improved through low-temperature plasma modification technology, and ZnS:Mn friction luminescent materials are prepared in high-temperature solid phase reaction, which solves the problem of insufficient friction luminescent intensity, achieves higher brightness friction luminescent performance, and expands its Application field.
Patent Information
- Application Number
- CN202411407378.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-18
AI Technical Summary
The insufficient friction luminescent intensity of ZnS:Mn friction luminescent materials limits their application in the fields of mechanical equipment health monitoring and stress visualization.
The surface of ZnS particles is improved by low-temperature plasma modification technology, and then high-temperature solid phase reaction is carried out under a protective atmosphere to prepare a ZnS:Mn friction luminescent material with high brightness friction luminescent performance.
The friction luminescence performance of ZnS:Mn friction luminescent materials has been improved, making their applications more flexible and reliable in the fields of mechanical equipment health monitoring and stress visualization.
Smart Images

Figure CN119463855A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of triboluminescent materials, and in particular to a ZnS:Mn triboluminescent material, a ZnS-based triboluminescent composite solid lubricating material, and a preparation method and application thereof. Background Art
[0002] Triboluminescence is a phenomenon in which materials emit light when subjected to external mechanical stimuli such as friction, compression, and stretching. This unique force-light conversion property makes triboluminescent materials widely used in structural health monitoring, biomechanical sensing, smart lubrication, and smart wearables. Among them, ZnS has a wide direct band gap and can effectively excite the luminescence center of doped Mn ions. This wide excitation energy range makes ZnS:Mn more flexible and reliable in practical applications. However, the triboluminescence intensity of ZnS:Mn still needs to be improved, which is expected to improve its application in the fields of mechanical equipment health monitoring and stress visualization. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide a ZnS:Mn triboluminescent material, a ZnS-based triboluminescent composite solid lubricant, and a preparation method and application thereof. The present invention improves the triboluminescent performance of ZnS:Mn by low-temperature plasma modification.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing a ZnS:Mn triboluminescent material, comprising the following steps:
[0006] The ZnS particles are subjected to low temperature plasma modification to obtain modified ZnS;
[0007] The modified ZnS, MnCl2, elemental sulfur and a co-solvent are mixed and then subjected to a high-temperature solid-phase reaction under a protective atmosphere to obtain the ZnS:Mn triboluminescent material.
[0008] Preferably, the particle size of the ZnS particles is 200-500 nm.
[0009] Preferably, the conditions for low-temperature plasma modification include: vacuum degree of 5-9 Pa, power duty cycle of 29.7%, voltage power of 6-15 kV, plasma gas of argon, processing time of 1-2 h, and temperature of 90-105° C.
[0010] Preferably, the ratio of the mass of the modified ZnS to the total mass of modified ZnS, MnCl2, elemental sulfur and co-solvent is (0.500-0.990):1; the ratio of the mass of the MnCl2 to the total mass of modified ZnS, MnCl2, elemental sulfur and co-solvent is (0.005-0.008):1; the ratio of the mass of the elemental sulfur to the total mass of modified ZnS, MnCl2, elemental sulfur and co-solvent is (0.001-0.005):1; the ratio of the mass of the co-solvent to the total mass of modified ZnS, MnCl2, elemental sulfur and co-solvent is (0.001-0.004):1.
[0011] Preferably, the temperature of the high-temperature solid-phase reaction is 950-1200°C, the insulation time is 2-5h, the pressure is 0.01-0.05MPa, and the heating rate from room temperature to the temperature of the high-temperature solid-phase reaction is 3.5-5.5°C / min.
[0012] The present invention also provides a ZnS:Mn triboluminescent material prepared by the preparation method described in the above technical solution.
[0013] The present invention also provides a method for preparing a ZnS-based triboluminescent composite solid lubricating material, comprising the following steps:
[0014] The ZnS:Mn triboluminescent material described in the above technical solution is compounded with polytetrafluoroethylene (PTFE), and then cold pressed and hot-sintered in sequence to obtain the ZnS-based triboluminescent composite solid lubricating material.
[0015] Preferably, the thermal sintering includes a first thermal sintering stage and a second thermal sintering stage which are carried out sequentially, wherein the sintering temperature of the first thermal sintering stage is 325-335°C, the holding time is 55-70min, and the heating rate from room temperature to the sintering temperature of the first thermal sintering stage is 1-3°C / min; the sintering temperature of the second thermal sintering stage is 370-380°C, the holding time is 130-140min, and the heating rate from the sintering temperature of the first thermal sintering stage to the sintering temperature of the second thermal sintering stage is 1-3°C / min.
[0016] The present invention also provides a ZnS-based triboluminescent composite solid lubricating material prepared by the preparation method described in the above technical solution.
[0017] The present invention also provides the application of the ZnS-based triboluminescent composite solid lubricating material described in the above technical solution in the field of friction lubrication.
[0018] The invention provides a method for preparing a ZnS:Mn triboluminescent material, comprising the following steps: subjecting ZnS particles to low-temperature plasma modification to obtain modified ZnS; and mixing the modified ZnS, MnCl2, elemental sulfur and a co-solvent, and subjecting the mixture to a high-temperature solid-phase reaction under a protective atmosphere to obtain the ZnS:Mn triboluminescent material.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] Low-temperature plasma modification is a technology that uses electric field to ionize gas to obtain high-energy ions and free electrons with positive and negative charges to treat the surface of materials, aiming to improve the physical, chemical and biological properties of the material surface. Since high-energy plasma will produce defects on the surface when bombarding inorganic powders, this can change the surface properties of the material. And plasma modification is a dry treatment process that does not require the use of a large amount of water and chemical reagents, and has environmental advantages. The present invention introduces low-temperature plasma technology into the preparation process of inorganic triboluminescent materials, aiming to improve the crystallinity of the materials, and provides a new method for improving the performance of triboluminescent materials. The ZnS:Mn triboluminescent material prepared by the present invention has high-brightness triboluminescent properties.
[0021] The present invention also provides a method for preparing a ZnS-based triboluminescent composite solid lubricant. After compounding a high-brightness ZnS:Mn triboluminescent material with PTFE, a composite solid lubricant with triboluminescent properties is prepared by cold pressing and hot sintering. This will greatly expand the application of ZnS-based triboluminescent materials in the field of friction monitoring. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A schematic diagram of a low-temperature plasma device used for modifying ZnS in the present invention;
[0023] Figure 2 The force triboluminescence spectrum of the ZnS:Mn triboluminescent composite solid lubricant prepared in Examples 1 to 4 under the same conditions;
[0024] Figure 3 TEM diffraction spot patterns of unmodified ZnS and the ZnS:Mn triboluminescent material obtained in Example 2. DETAILED DESCRIPTION
[0025] The present invention provides a method for preparing a ZnS:Mn triboluminescent material, comprising the following steps:
[0026] The ZnS particles are subjected to low temperature plasma modification to obtain modified ZnS;
[0027] The modified ZnS, MnCl2, elemental sulfur and a co-solvent are mixed and then subjected to a high-temperature solid-phase reaction under a protective atmosphere to obtain the ZnS:Mn triboluminescent material.
[0028] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.
[0029] The invention performs low-temperature plasma modification on ZnS particles to obtain modified ZnS.
[0030] In the present invention, the particle size of the ZnS particles is preferably 200-500 nm, more preferably 400-500 nm, and specifically can be 200, 300, 400 or 500 nm.
[0031] In the present invention, the conditions for low-temperature plasma modification preferably include: a vacuum degree of 5 to 9 Pa, specifically 5, 6, 7, 8 or 9 Pa, a power duty cycle of 29.7%, a voltage power of 6 to 15 kV, specifically 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 KV, a plasma gas of argon, a treatment time of 1 to 2 h, specifically 1 or 2 h, a temperature of 90 to 105 ° C, specifically 90, 95, 100 or 105 ° C. Changing the conditions for low-temperature plasma modification, such as voltage power and time, can affect the modification effect of plasma on the ZnS surface.
[0032] After obtaining the modified ZnS, the present invention mixes the modified ZnS, MnCl2, elemental sulfur and a co-solvent, and then performs a high-temperature solid-phase reaction under a protective atmosphere to obtain the ZnS:Mn triboluminescent material.
[0033] In the present invention, the ratio of the mass of the modified ZnS to the total mass of the modified ZnS, MnCl2, elemental sulfur and the co-solvent is preferably (0.500-0.990):1, specifically 0.500:1, 0.600:1, 0.700:1, 0.800:1 or 0.9890:1; the ratio of the mass of the MnCl2 to the total mass of the modified ZnS, MnCl2, elemental sulfur and the co-solvent is preferably (0.005-0.008):1, specifically 0.005:1, 0.006:1, 0.007:1 or 0.9890:1. 008:1; the ratio of the mass of the elemental sulfur to the total mass of the modified ZnS, MnCl2, the elemental sulfur and the co-solvent is preferably (0.001-0.005):1, specifically 0.001:1, 0.002:1, 0.003:1, 0.004:1 or 0.005:1; the ratio of the mass of the co-solvent to the total mass of the modified ZnS, MnCl2, the elemental sulfur and the co-solvent is preferably (0.001-0.004):1, specifically 0.001:1, 0.002:1, 0.003:1 or 0.004:1.
[0034] In the present invention, the mixing preferably further comprises wet grinding, and the liquid medium of the wet grinding is preferably ethanol. The present invention has no particular limitation on the amount of the ethanol.
[0035] The endpoint of the wet grinding is preferably that the ethanol is completely volatilized.
[0036] In the present invention, the temperature of the high temperature solid phase reaction is preferably 950-1200°C, specifically 950, 1000, 1050, 1100, 1150 or 1200°C, the insulation time is preferably 2-5h, specifically 2, 3, 4 or 5h, the pressure is preferably 0.01-0.05MPa, specifically 0.01, 0.02, 0.03, 0.04 or 0.05MPa, and the heating rate from room temperature to the temperature of the high temperature solid phase reaction is preferably 3.5-5.5°C / min, specifically 3.5, 4, 4.5, 5 or 5.5°C / min.
[0037] In the present invention, the protective atmosphere is preferably nitrogen.
[0038] After the high-temperature solid-phase reaction is completed, the present invention preferably sequentially performs a first cooling, a second cooling to room temperature and a grinding on the obtained product to obtain the ZnS:Mn triboluminescent material.
[0039] In the present invention, the cooling rate of the first cooling is preferably 4-5.5°C / min, specifically 4, 4.5, 5 or 5.5°C / min, and the final temperature of the first cooling is preferably 500°C; the second cooling is preferably natural cooling.
[0040] The present invention has no particular limitation on the specific parameters of the grinding, as long as powder is obtained.
[0041] The present invention also provides a ZnS:Mn triboluminescent material prepared by the preparation method described in the above technical solution.
[0042] The present invention also provides a method for preparing a ZnS-based triboluminescent composite solid lubricating material, comprising the following steps:
[0043] The ZnS:Mn triboluminescent material described in the above technical solution is compounded with polytetrafluoroethylene (PTFE), and then cold pressed and hot-sintered in sequence to obtain the ZnS-based triboluminescent composite solid lubricating material.
[0044] In the present invention, the mass ratio of the ZnS:Mn triboluminescent material to polytetrafluoroethylene is preferably 0.5 to 1:1, more preferably 1:1.
[0045] In the present invention, the composite preferably comprises mechanically stirring the ZnS:Mn triboluminescent material and polytetrafluoroethylene in sequence, separating the dispersant and drying.
[0046] In the present invention, the dispersant used for the mechanical stirring is preferably ethanol, the rotation speed of the mechanical stirring is preferably 800-1200 rpm, specifically 800, 900, 1000, 1100 or 1200 rpm, and the time is preferably 1-3 h, specifically 1, 2 or 3 h.
[0047] In the present invention, the separation and dispersing agent is preferably suction filtration.
[0048] In the present invention, the drying is preferably carried out in an oven, and the drying time is preferably 24 hours. The present invention has no particular limitation on the drying temperature, as long as the solvent can be completely removed.
[0049] In the present invention, the drying preferably further includes low-temperature treatment, and the role of the low-temperature treatment is to prevent agglomeration.
[0050] In the present invention, the temperature of the low temperature treatment is preferably 1-4°C, specifically 1, 2, 3 or 4°C, and the time is preferably 24 hours. The low temperature treatment is preferably carried out in a refrigerator.
[0051] In the present invention, the cold pressing pressure is preferably 40-60 MPa, specifically 40, 50 or 60 MPa, the temperature is preferably room temperature, i.e. no additional heating or cooling is required, and the holding time is preferably 2-5 min, specifically 2, 3, 4 or 5 min.
[0052] In the present invention, the thermal sintering preferably includes a first thermal sintering stage and a second thermal sintering stage carried out in sequence. The sintering temperature of the first thermal sintering stage is preferably 325-335°C, specifically 325, 330 or 335°C, the holding time is preferably 55-70min, specifically 55, 60, 65 or 70min, and the heating rate from room temperature to the sintering temperature of the first thermal sintering stage is preferably 1-3°C / min, specifically 1, 1.5, 2 or 3°C / min; the sintering temperature of the second thermal sintering stage is preferably 370-380°C, specifically 370, 375 or 380°C, the holding time is preferably 130-140min, specifically 130, 135 or 140min, and the heating rate from the sintering temperature of the first thermal sintering stage to the sintering temperature of the second thermal sintering stage is preferably 1-3°C / min, specifically 1, 2 or 3°C / min.
[0053] After the sintering is completed, it is preferred to further include naturally cooling to room temperature to obtain the ZnS-based triboluminescent composite solid lubricating material.
[0054] The present invention also provides a ZnS-based triboluminescent composite solid lubricating material prepared by the preparation method described in the above technical solution.
[0055] The present invention also provides the application of the ZnS-based triboluminescent composite solid lubricating material described in the above technical solution in the field of friction lubrication.
[0056] The present invention has no particular limitation on the specific manner of the application, and any manner familiar to those skilled in the art may be used.
[0057] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0058] The particle size of the ZnS particles used in the embodiment of the present invention is 400-500 nm.
[0059] Figure 1 Schematic diagram of the low-temperature plasma device used for modifying ZnS in the present invention.
[0060] Example 1
[0061] The preparation method of low-temperature plasma surface modified ZnS is as follows: First, weigh 17g of ZnS particles and place them in a standard gauze sieve with a pore size of 0.3mm, and disperse them in an iron box with a size of length, width, and height = 30cm×22cm×3cm by knocking, and the powder thickness is 1mm. The iron box containing nano ZnS powder is placed in the sample chamber of the low-temperature plasma modification device, and argon gas is ionized to form argon ions using a 6kV radio frequency voltage, the power supply duty cycle is 29.7%, the vacuum degree is 9Pa, and the temperature is 100°C, so that it bombards the ZnS surface for 2h to obtain modified ZnS.
[0062] Weigh the above 24.3675g of modified ZnS, 0.1589g of MnCl2, 0.0732g of NaCl and 0.0401g of S in a mortar, add 5mL of ethanol and grind until the ethanol is completely volatilized. The obtained mixture is placed in a crucible and sintered in a tube furnace. The sintering temperature is 1150℃, the heating rate from room temperature to 1150℃ is 4.5℃ / min, the sintering time is 3h, the inert protective gas is nitrogen, and the pressure is 0.03MPa. After sintering, first cool to 500℃ at a rate of 4.5℃ / min, turn off the nitrogen, and then cool naturally to room temperature. After the sample is ground into powder, it is mixed with PTFE in ethanol by mechanical stirring at a mass ratio of 1:1, the speed is 900rpm, and the time is 1h. Then the mixed suspension is filtered to obtain a solid mixture. The mixture was placed in an oven for drying for 24 hours; after drying, it was placed in a refrigerator for low-temperature treatment for 24 hours. The solid mixture was pressed at room temperature and 50 MPa for 3 minutes, and then placed in a muffle furnace for calcination. The temperature was raised to 330°C at a rate of 1.5°C / min and kept at that temperature for 60 minutes, and then raised to 375°C at a rate of 1°C / min and kept at that temperature for 130 minutes, and then cooled to room temperature to obtain ZnS:Mn / PTFE.
[0063] Example 2
[0064] The "using a 6 kV RF voltage to ionize argon gas to form argon ions" in Example 1 was replaced by "using a 9 kV RF voltage to ionize argon gas to form argon ions", and the other preparation conditions were the same as in Example 1 to obtain ZnS:Mn / PTFE.
[0065] Example 3
[0066] The "using a 6 kV RF voltage to ionize argon gas to form argon ions" in Example 1 was replaced by "using a 12 kV RF voltage to ionize argon gas to form argon ions", and the other preparation conditions were the same as in Example 1 to obtain ZnS:Mn / PTFE.
[0067] Example 4
[0068] The "using a 6 kV RF voltage to ionize argon gas to form argon ions" in Example 1 was replaced by "using a 15 kV RF voltage to ionize argon gas to form argon ions", and the other preparation conditions were the same as in Example 1 to obtain ZnS:Mn / PTFE.
[0069] Example 5
[0070] The "power duty cycle is 29.7%, the vacuum degree is 9 Pa, the temperature is 100°C, and it bombards the ZnS surface for 2 hours" in Example 1 is replaced by "power duty cycle is 29.7%, the vacuum degree is 9 Pa, and it bombards the ZnS surface for 1 hour," and the other preparation conditions are the same as in Example 1 to obtain ZnS:Mn / PTFE.
[0071] Figure 2 The triboluminescence spectra of the ZnS:Mn triboluminescent composite solid lubricant prepared in Examples 1 to 4 under the same conditions show that the triboluminescence performance of ZnS:Mn prepared by sintering ZnS treated with plasma as a raw material is improved, and the best voltage is 12 kV.
[0072] Figure 3 TEM diffraction spot diagram of unmodified ZnS and ZnS:Mn triboluminescent material obtained in Example 2. It can be seen that after the surface of ZnS is modified by plasma, the crystallinity of the obtained ZnS:Mn is better.
[0073] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a ZnS:Mn triboluminescent material, characterized in that: The following steps are involved: The ZnS particles are subjected to low temperature plasma modification to obtain modified ZnS; The modified ZnS, MnCl2, elemental sulfur and a co-solvent are mixed and then subjected to a high-temperature solid-phase reaction under a protective atmosphere to obtain the ZnS:Mn triboluminescent material.
2. The preparation method according to claim 1, characterized in that: The particle size of the ZnS particles is 200-500 nm.
3. The preparation method according to claim 1 or 2, characterized in that: The conditions for low-temperature plasma modification include: vacuum degree of 5-9 Pa, power duty cycle of 29.7%, voltage power of 6-15 kV, plasma gas of argon, processing time of 1-2 hours, and temperature of 90-105° C.
4. The preparation method according to claim 1, characterized in that: The ratio of the mass of the modified ZnS to the total mass of the modified ZnS, MnCl2, elemental sulfur and the co-solvent is (0.500-0.990):1; the ratio of the mass of the MnCl2 to the total mass of the modified ZnS, MnCl2, elemental sulfur and the co-solvent is (0.005-0.008):1; the ratio of the mass of the elemental sulfur to the total mass of the modified ZnS, MnCl2, elemental sulfur and the co-solvent is (0.001-0.005):1; the ratio of the mass of the co-solvent to the total mass of the modified ZnS, MnCl2, elemental sulfur and the co-solvent is (0.001-0.004):
1.
5. The preparation method according to claim 1, characterized in that: The temperature of the high-temperature solid-phase reaction is 950-1200°C, the insulation time is 2-5h, the pressure is 0.01-0.05MPa, and the heating rate from room temperature to the temperature of the high-temperature solid-phase reaction is 3.5-5.5°C / min.
6. The ZnS:Mn triboluminescent material obtained by the preparation method according to any one of claims 1 to 5.
7. A method for preparing a ZnS-based triboluminescent composite solid lubricant, characterized in that: The following steps are involved: The ZnS:Mn triboluminescent material according to claim 6 is compounded with polytetrafluoroethylene, and then cold pressed and hot-sintered in sequence to obtain the ZnS-based triboluminescent composite solid lubricant.
8. The preparation method according to claim 7, characterized in that: The thermal sintering includes a first thermal sintering stage and a second thermal sintering stage which are carried out sequentially. The sintering temperature of the first thermal sintering stage is 325-335°C, the holding time is 55-70min, and the heating rate from room temperature to the sintering temperature of the first thermal sintering stage is 1-3°C / min; the sintering temperature of the second thermal sintering stage is 370-380°C, the holding time is 130-140min, and the heating rate from the sintering temperature of the first thermal sintering stage to the sintering temperature of the second thermal sintering stage is 1-3°C / min.
9. The ZnS-based triboluminescent composite solid lubricating material prepared by the preparation method according to claim 7 or 8.
10. Use of the ZnS-based triboluminescent composite solid lubricant according to claim 9 in the field of friction and lubrication.